ZIF‐67 Loaded on Fe3O4‐MnO2 as Efficient Peroxymonosulfate Activator for Rapid Degradation of Carbamazepine. Issue 11 (9th May 2021) - Dong, Limei; Li, Yiming; Chen, Xiuping; Zhang, Dan; Guan, Yihao
Abstract: Poor sorption capacity and low biodegradability of carbamazepine (CBZ) lead to the difficulties in CBZ removal from water. Sulfate radical‐based advanced oxidation process shows great potential for organic pollutant removal. Metal organic frameworks (MOFs) demonstrate great potential in catalytic field due to their excellent properties. Hence, cobalt‐based metal organic framework (ZIF‐67) nanoparticles are loaded on Fe3 O4 ‐MnO2 composite, and then this composite is applied as peroxymonosulfate (PMS) activator for CBZ degradation. The prepared catalyst exhibits excellent catalytic performance because of the central metal cobalt of ZIF‐67 and the synergistic effect between MnO2 and ZIF‐67. 81% of CBZ with a high initial concentration of 20 mg L −1 is rapidly removed from water within 2.5 min. The prepared catalyst can be convenient to recycle under magnetic field while maintaining its high catalytic stability. Degradation mechanism analysis indicates that both OH and SO4 − contribute to CBZ degradation, but SO4 − is the main radical species. XPS spectra reveal that Co(II)/Co(III), Mn(II)/Mn(III)/Mn(IV), and Fe(II)/Fe(III) are involved in PMS activation. The degradation pathway is put forward based on the detection of intermediates. This study provides a new inspiration for the fabrication of magnetic metal oxide‐MOFs catalysts with outstanding recycling performance for PMS activation. Abstract : The hierarchically structured Fe3 O4 ‐MnO2 ‐ZIF‐67 composite is prepared and applied for activating peroxymonosulfate to degrade carbamazepine (CBZ). The prepared catalyst exhibits extremely rapid removal of CBZ. The SO4 − and OH jointly lead to the efficient degradation of CBZ. In a word, Fe3 O4 ‐MnO2 ‐ZIF‐67 is a promising catalytic material for the removal of organic pollutants from water.